Comparando la Norma Anti-elusiva General de la Ley del Impuesto a la Renta con la Doctrina de Abuso de Derecho del Civil Law (Parte II) - Prebble, Zoë; Prebble, John (Pontificia Universidad Católica del Perú, 2015)
This article compares and analyzes how member States of the European Union, the United States of America and the United Kingdom combat tax avoidance through its legal systems. The article addresses issues such as the influence of the Court of Justice of the European Union and the case Cadbury Schweppes in establishing anti-avoidance rules in member States of the European Union and the application of Business Purpose Doctrine in the United States of America and the United Kingdom.

El presente artículo compara y analiza la manera en que los Estados miembros de la Unión Europea, los Estados Unidos y el Reino Unido combaten la elusión tributaria a través de sus sistemas legales. El artículo aborda temas como la influencia del Tribunal de Justicia de la Unión Europea y el caso Cadbury Schweppes en el establecimiento de normas antielusivas en los Estados miembros de la Unión Europea, y la aplicación de la doctrina de la simulación en los Estados Unidos y en el Reino Unido.
Comparing the General Anti-avoidance Rule of Income Tax Law with the Civil Law Doctrine of Abuse of Law (Part II)
Keywords: Anti-Avoidance Provisions; Income Tax; Abuse Of Rights; European Union; Case Cadbury Schweppes; United States Of America; United Kingdom; Business Purpose Doctrine; Normas Antielusivas; Impuesto a la renta; Abuso de derecho; Unión Europea; Caso Cadbury Schweppes; Estados Unidos; Reino Unido; Doctrina de la simulación; https://purl.org/pe-repo/ocde/ford#5.05.00